(untitled) (Philological Studies, 2019)
Characteristics of the Beat literature inspired South Slavic authors, although the Beat reception was not systematically studied and researched in any of the South Slavic literatures. We deals with reception through exchange of experiences in the journeys of the Beat authors to ex-Yugoslavian countries and vice versa. Here two slightly forgotten South Slavic authors, whose expression is the most similar to the Beats – Milan Oklopdžić and Vojo Šindolić are introduced, dubbed to be Ginsberg and Kerouc of the South Slavic area. Common sensibility and worldview similarities are visible in the certain creative stages of Vojislav Despotov’s work, his „scream blown into a balloon“ and jazz poetry Ten Decagrams of Soul for example, and works of Vladimir Kopicl and extremely subversive author Tomaž Šalamun.